PROGRAM GERAKAN REMAJA CEGAH STUNTING (GERAH STUNTING) PADA SEKOLAH TINGKAT SMP DAN SMA DI KABUPATEN CIAMIS - Asep Alpurqon; Deni Rizky Supriatna; Lilis Karwati; Nastiti Novitasari (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Gerah Stunting is an extension program given to adolescents as agents of change in the context of preventing and reducing stunting rates, especially in the Ciamis Regency. This encourages studies on increasing public understanding regarding stunting prevention. This program is to provide education to adolescents to minimize stunting problems. The movement program to prevent stunting includes providing counseling related to Mahat Genting (Healthy Food, Movement to Prevent Stunting), and Important (Proper Parenting). Prevent Stunting), Hot Stunting (Adolescent Movement to Prevent Stunting and also the Genting Center (Healthy Living Behavior Prevents Stunting). The aim is to increase youth knowledge about the concept of Prevention of Adolescent Stunting, Adolescent PHBS, HIV/AIDS, Drug Dangers, Introduction to Education, and Introduction to Genre and PIK-R forums. So that Middle and High School levels can be provided in running a healthy life.